THE TOMB OF RAMBAN BIAQ MYTHOLOGY IN RAMBAN BIAQ VILLAGE, EAST LOMBOK - Badarudin, Badarudin; Hafiz, Abdul; Rasyad, Abdul; Alfarisi, Salman; Rizkah, Rizkah (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This study focused on examining mythology and history of tomb for a person who was considered sacred by the society. The sacred tomb is the place where person factually buried or the last location seen by others according to the local people beliefs of a past figure based on the relationships of ancestral, great name, extraordinary advantages, historical traces, his services, and values and traditions inherited by the figure which is believed by the most people to grant the wishes. The sacred tomb is the tomb of a figure in the past such as wali Allah, king, and so on. The purpose of this study was to know the history of the tomb of Ramban Biaq in East Lombok, to understand the people perception of the tomb of Ramban Biaq, to know the factors influencing people to make a pilgrimage to the tomb of Ramban Biaq, and to understand the procedures of pilgrimage to the tomb of Ramban Biaq. This study used a qualitative method with a phenomenological approach. Data were collected by observation, interviews, and literature study. The result study explained that the person who was featured in the mythology of the tomb of Ramban Biaq did not die, but still alive and lived in another world. The other myth was that this tomb can grant a pray to God.Â